ANALISIS PEMAHAMAN SISWA PADA MATERI SEL TERHADAP PENERAPAN KURIKULUM 2013 PADA SISWA KELAS XI SMA SWASTA KAMPUS TELUK DALAM - Nita Dewi Tafonao (TUNAS : Jurnal Pendidikan Biologi, 2024)
This research aims to analyze students’ understanding of cell material towards the implementation of the 2013 curriculum in class XI students at the Teluk Dalam Campus private high school. The type of research used in this research is qualitative research with a descriptive approach by conducting a study of the data obtained. Data collection in this research was by direct interviews with teachers and students. The data analysis used is data reduction, data presentation, and drawing conclusions. Based on the results of the research above which has been carried out by researchers, it can be seen that students’ understanding of cell material towards the implementation of the 2013 curriculum in class This cannot be separated from the teacher’s role in implementing a creative and innovative learning process through learning models and methods as well as the curriculum applied in the teaching and learning activities carried out. From the results of observations that have been made through tests, especially on cell material with the implementation of the 2013 curriculum, students do not experience problems in solving the questions given.